1997
DOI: 10.1074/jbc.272.10.6332
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Smooth Muscle Myosin Heavy Chain Gene Is Regulated by a Negative-acting GC-rich Element Located between Two Positive-acting Serum Response Factor-binding Elements

Abstract: To identify cis-and trans-acting factors that regulate smooth muscle-specific gene expression, we studied the smooth muscle myosin heavy chain gene, a rigorous marker of differentiated smooth muscle. A comparison of smooth muscle myosin heavy chain promoter sequences from multiple species revealed the presence of a highly conserved 227-base pair domain (nucleotides ؊1321 to ؊1095 in rat). Results of a deletion analysis of a 4.3-kilobase pair segment of the rat promoter (nucleotides ؊4220 to ؉88) demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 50 publications
4
105
1
Order By: Relevance
“…The association of decreases in Sp1 binding with promoter activation at first seemed paradoxical. However, other investigators have shown that, in contrast to its accepted role as a homeostatic transactivator (14,15), Sp1 binding can sometimes function as a gene repressor (16,17). Our results demonstrate that the proximal Sp1 binding site in the TNF-␣ promoter can function as a repressor element.…”
Section: Functional Analysis Of Sp1 Binding Sites In a Heterologoussupporting
confidence: 44%
See 1 more Smart Citation
“…The association of decreases in Sp1 binding with promoter activation at first seemed paradoxical. However, other investigators have shown that, in contrast to its accepted role as a homeostatic transactivator (14,15), Sp1 binding can sometimes function as a gene repressor (16,17). Our results demonstrate that the proximal Sp1 binding site in the TNF-␣ promoter can function as a repressor element.…”
Section: Functional Analysis Of Sp1 Binding Sites In a Heterologoussupporting
confidence: 44%
“…Similar to CRE-binding proteins, cAMP-dependent protein kinase (PKA) phosphorylation of Sp1 has been shown to enhance its DNA binding activity (13). Although Sp1 binding can activate transcription (14,15), for some genes Sp1 functions as a repressor (16,17). The promoter motifs or cell characteristics that determine these divergent effects of Sp1 binding are not fully understood.…”
mentioning
confidence: 99%
“…12 The rat SMMHC promoter contains a negative regulatory GC-rich element (CCCGCCC), mutation of which increases expression of CAT in SMC by 100%. 15 The same sequence is present in the ME sequence.…”
Section: Discussionmentioning
confidence: 97%
“…These include the rat D 2 dopamine promoter (43), the rat ␣ 2 A adrenergic promoter (44), the long terminal receptor of the human T cell leukemia virus type I promoter (45), the rat fatty acid synthase promoter (46), and the rat smooth muscle myosin heavy chain promoter (47). The finding that the GC or GT box is involved in the negative regulation of gene expression implies that the GC or GT box may play a more complicated role in transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%